2021
DOI: 10.1016/j.jclepro.2020.123582
|View full text |Cite
|
Sign up to set email alerts
|

A model for partner selection criteria in energy from waste projects

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…The cross-check in the Scopus database suggested two main streams of the current success studies, and both indicated focusing and narrowing. The first stream is related to the particular type of engineering project, such as highway construction (Alleman and Tran 2021;Choi et al 2020), power sites (Abdel-Basset et al 2021), petroleum and petrochemical industry (Faraji et al 2021;Shariatfar et al 2019), space industry (Decadi 2021), waste treatment (Uren et al 2021), or IT (Hussain et al 2021). Significant research was conducted of highway construction projects, in which a link between contracting methods and criteria such as schedule, cost, and change orders was investigated (Choi et al 2020), as well as procurement method (Alleman and Tran 2021).…”
Section: Cross-check With Most Recent Studiesmentioning
confidence: 99%
“…The cross-check in the Scopus database suggested two main streams of the current success studies, and both indicated focusing and narrowing. The first stream is related to the particular type of engineering project, such as highway construction (Alleman and Tran 2021;Choi et al 2020), power sites (Abdel-Basset et al 2021), petroleum and petrochemical industry (Faraji et al 2021;Shariatfar et al 2019), space industry (Decadi 2021), waste treatment (Uren et al 2021), or IT (Hussain et al 2021). Significant research was conducted of highway construction projects, in which a link between contracting methods and criteria such as schedule, cost, and change orders was investigated (Choi et al 2020), as well as procurement method (Alleman and Tran 2021).…”
Section: Cross-check With Most Recent Studiesmentioning
confidence: 99%
“…According to [71][72][73][74], sustainable development actions can be divided into three main groups or dimensions: economic, social, and environmental (Figure 2).…”
Section: Adopted Criteriamentioning
confidence: 99%
“…According to [71][72][73][74], sustainable development actions main groups or dimensions: economic, social, and environme From the literature, and regarding the criteria normally u CNs, we have found a set of criteria, which we have categor dimensions defined before, i.e.,: From the literature, and regarding the criteria normally used in partner selection for CNs, we have found a set of criteria, which we have categorized, according to the three dimensions defined before, i.e.,:…”
Section: Adopted Criteriamentioning
confidence: 99%
See 1 more Smart Citation